Unveiling the hidden world of transfer RNA-derived small RNAs in inflammation - Peiru Qiu; Qi Jiang; Haojun Song (BMC, 2024)
Abstract Transfer RNA-derived small RNAs (tsRNAs) are a newly discovered class of small noncoding RNAs (sncRNAs) that include tRNA-derived stress-induced RNAs (tiRNAs) and tRNA-derived fragments (tRFs). Following the development of high-throughput sequencing technology, an increasing number of tsRNAs have been discovered with vital functions in different physiological and pathophysiological processes. Extensive research has revealed that tsRNAs are involved in various diseases, such as cancers, autoimmune illnesses and other diseases. This review focuses on the role and significance of tsRNAs in inflammation, such as the regulation of substances including inflammatory inducers, inflammatory cells and inflammatory factors, which contribute to the pathogenesis of inflammation-related diseases. Moreover, we discuss in-depth the molecular pathogenic mechanisms of tsRNAs in inflammation-related diseases through different signaling pathways and assess their clinical value, providing new perspectives for the exploration of tsRNA functions and inflammation-related diseases.